Delivery of Outpatient Parenteral Antimicrobial Therapy (OPAT) in an Ever-Changing National Health Service (UK): Benefits, Barriers, and Opportunities - Oyewole Christopher Durojaiye; Charlotte Fiori; Katharine Cartwright (Antibiotics)
Outpatient parenteral antimicrobial therapy (OPAT) is increasingly used to manage a broad range of infections, enabling patients to receive intravenous antibiotics safely outside inpatient settings. In this review, we examine the current landscape of OPAT practice across the United Kingdom (UK), assessing its clinical, economic, and operational impact. The benefits of OPAT for patients and the National Health Service (NHS), as well as its associated risks, are discussed. Additionally, we explore the challenges hindering its broader implementation within the UK. Finally, we highlight recent innovations and emerging applications of OPAT relevant to the NHS, underscoring key considerations for its future expansion and emphasising the need for a nationally coordinated strategy to realise its full potential.